Modul Bimbingan Konseling dalam Meningkatkan Kemampuan Merespon Pembelajaran Mahasiswa - Nasution, Syawaluddin; Sahputra, Dika (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
This research aims to formulate guidance and counseling modules to improve students’ responding activities when learning in class and to describe the level of applicability used by counselors. The method used was ADDIE model development. The properness test was done by three experts, and the practicality test was done by three counselors. The object of this research is students who have low criteria in terms of responding to learning. This research was conducted at the State Islamic University of North Sumatra, Medan. The instruments used were a questionnaire and focus group discussion (FGD). The data were analyzed descriptively. Based on these results, in general, it was concluded that the module developed was appropriate and could be used to help the students improve their responding activity when learning in class.